First shots of the climate revolution: An untold story - Roederer, Juan G. (Frontiers in Astronomy and Space Sciences, 2022)
This is an account of the history of the “climate revolution of the eighties”, focusing on early discussions and, at times, fierce disputes about what’s wrong with Planet Earth and why, and what to do about it through coordinated research. The paper describes the genesis and initial planning of the Global Change program within the International Council of Scientific Unions, and the early split of participating scientists into two camps: one emphasizing the need for a truly global, widely interdisciplinary and basic-science oriented approach that views the Earth system as one single whole of strongly interacting parts; the other camp defending a much more restricted approach by focusing exclusively on that which has greatest and most immediate impact on society. As a spin-off from the defeat of the “globalists” came the generation of yet another, ultimately international (and politically far less controversial) program, centered on what today is called Space Weather—the study of solar-variability- and human-induced changes in the space environment of Earth, and the ensuing effects on technological (and human) systems in space, as well as the possible physical downward actions of these space perturbations on our more immediate environment of air, water, land and biota.